The optimism effect on country productivity and innovation activities - Daniel Mahn; Cong Wang; Danielle Kent; Christopher Heaton (Journal of Innovation & Knowledge (JIK), 2024)
This study focuses on how optimism translates into innovation outcomes. While the link has been established at a microeconomic level, its translation to an aggregate economic effect is still an open question. Empirical analysis draws from a yearly sample of 42 (mainly OECD) countries between 2000 and 2020 to test the effect of economic optimism on R&D measures from both the consumer's and producer's points of view at the aggregate level. Using modern econometric techniques that address potential endogeneity issues, the results suggest that economic optimism supports an increase in innovation activity and economic performance but not an increase in innovation outcomes, such as more patent production. The implication is that an economically optimistic environment is an important contribution to a nation's entrepreneurial ecosystem. This novel insight shows that firms need not specifically recruit optimistic individuals to reap the benefits of the optimism effect. Policies that encourage economic optimism can orchestrate an environment in which the benefits of the optimism effect are realized, independent of the individual personality traits of its citizens.
Keywords: E70; G40; O30; 650; Entrepreneurial ecosystem; Productivity; Optimism; Innovation; R&D; Total factor productivity